The International Conference on Victorian and American Myths in Video Games - Teresa Pereira (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
The International Conference on Victorian and American Myths in Video Games and the Keynote Lectures